2008
DOI: 10.1071/fp07283
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sulfate uptake, expression of the sulfate transporters Sultr1;1 and Sultr1;2, and APS reductase in Chinese cabbage (Brassica pekinensis) as affected by atmospheric H2S nutrition and sulfate deprivation

Abstract: The activity and expression of sulfate transporters and adenosine 5′-phosphosulfate (APS) reductase (APR) in plants are modulated by the plant sulfur status and the demand for growth. To elucidate regulatory mechanisms in Chinese cabbage [Brassica pekinensis (Lour.) Rupr.], the interactions between atmospheric H2S and sulfate nutrition and the impact on the activity and expression of the Group 1 sulfate transporters and APR were studied. At an ample sulfate supply, H2S exposure of Chinese cabbage resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 34 publications
5
81
1
Order By: Relevance
“…Selenate supply had little effect on transcript abundance, and S starvation only resulted in a slight increase in the expression of group 1 and group 4 transporters in root tissues. This is in contrast to observations with other species, where the expression of many sulfate transporters has been shown to be highly induced by sulfate starvation (Smith et al, 1995(Smith et al, , 1997Takahashi et al, 2000;Shibagaki et al, 2002;Yoshimoto et al, 2002Yoshimoto et al, , 2003Howarth et al, 2003;Buchner et al, 2004aBuchner et al, , 2004bHopkins et al, 2004Hopkins et al, , 2005Koralewska et al, 2008Koralewska et al, , 2009Rouached et al, 2008;Shinmachi et al, 2010). The expression of one group 1 isoform, Sultr1;1, and one group 2 isoform, Sultr2;1, has also been shown to be induced by increased Se supply (Takahashi et al, 2000).…”
Section: Discussioncontrasting
confidence: 54%
“…Selenate supply had little effect on transcript abundance, and S starvation only resulted in a slight increase in the expression of group 1 and group 4 transporters in root tissues. This is in contrast to observations with other species, where the expression of many sulfate transporters has been shown to be highly induced by sulfate starvation (Smith et al, 1995(Smith et al, , 1997Takahashi et al, 2000;Shibagaki et al, 2002;Yoshimoto et al, 2002Yoshimoto et al, , 2003Howarth et al, 2003;Buchner et al, 2004aBuchner et al, , 2004bHopkins et al, 2004Hopkins et al, , 2005Koralewska et al, 2008Koralewska et al, , 2009Rouached et al, 2008;Shinmachi et al, 2010). The expression of one group 1 isoform, Sultr1;1, and one group 2 isoform, Sultr2;1, has also been shown to be induced by increased Se supply (Takahashi et al, 2000).…”
Section: Discussioncontrasting
confidence: 54%
“…However, several studies also showed the presence of their transcripts in shoots of S-deficient plants, suggesting a further function for S distribution into different cell types in different tissues (Koralewska et al, 2007;Ciaffi et al, 2013). In contrast to what has been suggested before (Parmar et al, 2007;Koralewska et al, 2008), SlST1.1 and SlST1.2 showed the same pattern of regulation in both shoots and roots of tomato plants (Fig. 3, A and B), suggesting that these transporters could be involved in the widespread and tissue-independent response to S deficiency.…”
Section: Determination Of Metabolite Levelsmentioning
confidence: 52%
“…This is in concordance with the fact that the control of expression of STs seems to be independent from OAS accumulation . With respect to the regulation of sulfate uptake, it has been proposed that the induction of STs is most likely triggered by changes in sulfate concentration (Koralewska et al, 2008), other than those in thiol compounds (Maruyama-Nakashita et al, 2004;Davidian and Kopriva, 2010). However, the molecular details underlying this mechanism remain unknown.…”
Section: Determination Of Metabolite Levelsmentioning
confidence: 99%
“…Sulfur deficiency directly affects a plant's primary metabolism, in large part through suppression of the photosynthetic machinery via decreased chlorophyll content and reduced synthesis of ribulose-1,5-bisphosphate carboxylase/oxygenase, restricting CO 2 assimilation (Burke et al, 1986;Gilbert et al, 1997). Concentrations of nonprotein thiol compounds and amino acid composition are also affected by S deprivation (Buchner et al, 2004;Koralewska et al, 2008;Khan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, plants are also capable of using atmospheric S, sulfur dioxide and H 2 S, to meet their S needs. These otherwise toxic volatiles are valuable S sources, particularly when S supply to the root is limited (DeKok et al, 1997;Stuiver and De Kok, 2001;Buchner et al, 2004;Durenkamp and De Kok, 2005;Koralewska et al, 2008;Chen et al, 2011). We show that exposure of wild-type and 35S-etr1 seedlings to the B55 VOC bouquet or DMDS dramatically increased seedling vigor (in terms of size, chlorophyll content, and root architecture) as well as the concentration of S-containing compounds (i.e., free Met and glutathiones [GSH and GSSG]) (Figures 1, 5, 6, and 9).…”
Section: Discussionmentioning
confidence: 99%